Stromal and epithelial caveolin-1 both confer a protective effect against mammary hyperplasia and tumorigenesis: Caveolin-1 antagonizes cyclin D1 function in mammary epithelial cells - Williams, Terence M; Sotgia, Federica; Lee, Hyangkyu; Hassan, Ghada; Di Vizio, Dolores; Bonuccelli, Gloria; Capozza, Franco; Mercier, Isabelle; Rui, Hallgeir; Pestell, Richard G; Lisanti, Michael P (The American journal of pathology, 2006)
Here, we investigate the role of caveolin-1 (Cav-1) in breast cancer onset and progression, with a focus on epithelial-stromal interactions, ie, the tumor microenvironment. Cav-1 is highly expressed in adipocytes and is abundant in mammary fat pads (stroma), but it remains unknown whether loss of Cav-1 within mammary stromal cells affects the differentiated state of mammary epithelia via paracrine signaling. To address this issue, we characterized the development of the mammary ductal system in Cav-1-/- mice and performed a series of mammary transplant studies, using both wild-type and Cav-1-/- mammary fat pads. Cav-1-/- mammary epithelia were hyperproliferative in vivo, with dramatic increases in terminal end bud area and mammary ductal thickness as well as increases in bromodeoxyuridine incorporation, extracellular signal-regulated kinase-1/2 hyperactivation, and up-regulation of STAT5a and cyclin D1. Consistent with these findings, loss of Cav-1 dramatically exacerbated mammary lobulo-alveolar hyperplasia in cyclin D1 Tg mice, whereas overexpression of Cav-1 caused reversion of this phenotype. Most importantly, Cav-1-/- mammary stromal cells (fat pads) promoted the growth of both normal mammary ductal epithelia and mammary tumor cells. Thus, Cav-1 expression in both epithelial and stromal cells provides a protective effect against mammary hyperplasia as well as mammary tumorigenesis.